International Relations, Music and Diplomacy Sounds and Voices on the International Stage (The Sciences Po Series in International Relations and Political Economy, 2018)
This volume explores the interrelation of international relations, music, and diplomacy from a multidisciplinary perspective. Throughout history, diplomats have gathered for musical events, and musicians have served as national representatives. Whatever political unit is under consideration (city-states, empires, nation-states), music has proven to be a component of diplomacy, its ceremonies, and its strategies. Following the recent acoustic turn in IR theory, the authors explore the notion of "musical diplomacies" and ask whether and how it differs from other types of cultural diplomacy. Accordingly, sounds and voices are dealt with in acoustic terms but are not restricted to music per se, also taking into consideration the voices (speech) of musicians in the international arena. Frédéric Ramel is Full Professor and Head of the Political Science Department at Sciences Po, Centre de Recherches Internationales, France. Cécile Prévost-Thomas is Associate Professor in Sociology of Music at the University Sorbonne Nouvelle - Paris 3, Centre de Recherche sur les Liens Sociaux, France.